A Case-Control Study Examining the Association of Fiber Intake and the Risk of Colorectal Cancer in a Palestinian Population. (29th May 2020) - Taha, Hania; Slade, Alexander; Schwartz, Betty; Arthur, Anna
Abstract: Objectives: Associations between diet and colorectal cancer (CRC) have not yet been examined in a population inhabiting the Palestinian territories, which are undergoing a nutrition transition. Understanding how diet may impact CRC risk among Palestinians is essential to developing targeted, culturally-relevant strategies that could alleviate the burden of this disease. The aim of this study was to examine how dietary fiber and fruit & vegetable (FV) intakes are associated with the risk of CRC among Palestinian adults recruited from a tertiary care facility in East Jerusalem. Methods: This was a case-control study of 528 Palestinian men and women >18 years old who were recruited from Augusta Victoria Hospital (AVH) between 2014 and 2016. Cases included 118 patients who were treated for CRC at AVH.  Controls included 410 individuals who consisted of a community-based sample of Palestinian individuals without cancer.  All participants completed a survey regarding demographics, CRC-related risk factors, and a validated food screener to assess intakes of dietary fiber and FV. Multivariable logistic regression models tested associations between dietary fiber and FV intakes (categorized into quartiles) with the risk of CRC, adjusting for sex, diabetes, family history of CRC, and inflammatory bowel disease. Results: After adjusting for covariates, as dietary fiber increased across quartiles of intake, the risk of CRC significantly decreased (OR for Q4 vs Q1 = 0.26, 95% CI: 0.12–0.58, p-trend = 0.0007). There was no significant association observed between FV intake and CRC risk. Conclusions: Consumption of high dietary fiber was associated with lower CRC risk in this case-control study of a Palestinian population. The development and testing of culturally-relevant dietary interventions to promote increasing dietary fiber intake among Palestinians are needed, particularly interventions targeting those at high risk for developing CRC. Funding Sources: USDA/NIFA Hatch Project 1, 011, 487 and a Pears Foundation Scholarship from the Robert H. Smith Faculty of Agriculture, Hebrew University of Jerusalem.